The carbon footprint wars : what might happen if we retreat from globalization? - Sim, Stuart (Edinburgh : Edinburgh University Press, 2009)
The Carbon Footprint Wars challenges current policies about how to deal with global warming, outlining their potentially disastrous side-effects on society and the environment and offers some radical solutions for dealing with climate change.
Acknowledgements; Preface; Part I: The Problems; 1. Introduction: The Carbon Footprint Wars: What is at Stake?; 2. Global Warming: The Evidence For; 3. Global Warming: The Arguments Against; 4. The Globalization Paradigm: Defenders and Detractors; Part II: The Solutions; 5. Reducing Our Carbon Footprint: Altering Lifestyles; 6. Living With Our Carbon Footprint: The Technological Response; Part III: The Consequences; 7. Worst-Case Scenarios: Economic; 8. Worst-Case Scenarios: Socio-Political; 9. Worst-Case Scenarios: Technological and Environmental; Part IV: Reassessing Global Priorities; 10. Reconstructing Geopolitical Relationships: The Ethical Dimension; 11. Reconstructing Geopolitical Narratives: A Radical Democratic Globe?; 12. Conclusion: Survival, Disaster, Trade-Off; Postscript; Notes; Bibliography.
Includes bibliographical references (p. 215-223) and index.
Keywords: Global warming; Climatic changes -- Environmental aspects; Climatic changes -- Government policy; Globalization -- Economic aspects